Keabsahan Calon Notaris dengan Kartu Tanda Anggota (Advokat) dalam Beracara di Pengadilan Sebelum Dilantik Menjadi Notaris - Jayantara, I Putu Agus Krisna; Jayantiari, I Gusti Agung Mas Rwa (Acta Comitas, 2025)
The study's goal is to examine the legal ramifications and professional ethics associated with prospective notaries holding an advocate membership card (KTA) in court proceedings.  The study methodology analyzes pertinent laws and legal ideas using a normative juridical approach.  According to the study's results, prospective notaries are legally permitted to function as advocates as long as they haven't been sworn in, but they must maintain their integrity and stay clear of conflicts of interest. However, the implication of not removing the Advocate Membership Card at the inauguration can lead to conflicts of interest and damage credibility.